An Integrated Framework of Spatiotemporal Dynamics of Binocular Rivalry - Kang, Min-Suk; Blake, Randolph (Frontiers in Human Neuroscience, 2011)
Fluctuations in perceptual dominance during binocular rivalry exhibit several hallmark characteristics. First, dominance switches are not periodic but, instead, stochastic: perception changes unpredictably. Second, despite being stochastic, average durations of rivalry dominance vary dependent on the strength of the rival stimuli: variations in contrast, luminance or spatial frequency produce predictable changes in average dominance durations and, hence, in alternation rate. Third, perceptual switches originate locally and spread globally over time, sometimes as traveling waves of dominance: rivalry transitions are spatio-temporal events. This essay 1) reviews recent advances in our understanding of the bases of these three hallmark characteristics of binocular rivalry dynamics and 2) provides an integrated framework to account for those dynamics using cooperative and competitive spatial interactions among local neural circuits distributed over the visual field’s retinotopic map. We close with speculations about how that framework might incorporate top-down influences on rivalry dynamics.